Presence of Escherichia coli O157:H7 in Chicken Meat at Traditional Markets in Pangkalpinang City - Ahmad Nurhakim; Denny Widaya Lukman; Herwin Pisestyani (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2022)
This study was aimed to identify the presence of E. coli O157:H7 and analyze the association between factors and frequency of E. coli in chicken meat sold at Kaget Market, Pagi Market, and Pembangunan Market in Pangkalpinang City. A total of 30 chicken meat samples were collected proportionally using simple random sampling. This study was used a cross sectional method. The examination of E. coli was carried out based on SNI 2897:2008 concerning The Testing Method of Microbial Contamination in Meat, Eggs, and Milk and Their Processed Products. The E. coli O157 was confirmed with O157 latex agglutination test and H7 antiserum test. The data were analyzed using a descriptive test and risk factors were analyzed using chi-square and odds ratio. The results showed that E. coli O157:H7 was found in 2 of 3 samples (66,7%) isolated from Kaget Market. The significant risk factors (P<0,005) for the presence of E. coli were traders with age of more 45 years, kiosk distance of less than 5 meters from the highway, and washing hands using unclean water. The presence of E. coli O157:H7 will be a threat for consumer health.